The most fabulous of libraries: that of Prester John in Ethiopia in the Early Seventeenth Century (Castilla. Estudios de Literatura, 2022)
In 1610 was published in Valencia the Historia eclesiástica, política, natural y moral de los grandes y remotos reynos de la Etiopía, Monarchía del Emperador, llamado Preste Iuan de las Indias. Its author was the Valencian Dominican Luis de Urreta and among the wonders of that fabulous kingdom stood out a fascinating library, of which the author tells us its origin, the richness of its manuscripts, the authors represented, the numerous works that it treasured, many of which were considered definitively lost, etc. peculiar embodiment of the Bibliotheca Universalis dreamed of by a friar brimming with medieval erudition.
Keywords: library; Prester John; Ethiopia; Dominicans; Jesuits; Modern age